A Brief School‐Based Cognitive‐Behavioral Intervention for Japanese Adolescents With Severe Posttraumatic Stress. Issue 6 (17th November 2016) - Ito, Daisuke; Koseki, Shunsuke; Ohtani, Tetsuhiro
Abstract: This pilot study investigated the efficacy of a brief school‐based cognitive–behavioral intervention program for Japanese adolescents exposed to the Great East Japan Earthquake in 2011. The participants were 22 adolescents with severe posttraumatic stress symptoms at the time of the study in March 2014. They completed a single‐session 4‐step intervention program based on Ehlers and Clark's (2000) model at their school. Symptom status was assessed at 3 time points (preintervention, postintervention, and 4‐month follow‐up) using the Impact of Event Scale‐Revised (Weiss, 2004) and Center for Epidemiologic Studies Depression Scale (Radloff, 1977). The results showed significant improvements in all posttraumatic stress symptoms at postintervention ( d = 0.81), and the effects were maintained throughout the 4‐month follow‐up period ( d = 1.10). However, no improvement in depressive symptoms was shown. Results from this pilot study suggest that school‐based cognitive–behavioral intervention programs are feasible and show promise for Japanese adolescents with posttraumatic stress symptoms regardless of cross‐cultural differences, but that additional research examining effectiveness is needed. Despite the preliminary nature of the findings of this pilot study, the strengths of our intervention were that it was driven by a well‐tested theoretical model and required only a single session to administer.